Voters as a hard budget constraint: on the determination of intergovernmental grants - Lars P. Feld; Christoph A. Schaltegger (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
Recent empirical literature has shown that the determination of intergovernmental grants is highly influenced by the political bargaining power of the recipient states. In these models federal politicians are assumed to buy the support of state voters, state politicians and state interest groups by providing grants. In this paper we provide evidence that the fiscal referendum reduces the reliance of states on matching grants received from the central government and thus the possibility of state interest groups and state bureaucrats to obtain more grants. If referendums are available, voters serve as a hard budget constraint.
Keywords: D7; D72; H77; 330; Budget Referendums; Intergovernmental Grants; Interest Group Influence; Finanzausgleich; Finanzföderalismus; Interessenpolitik; Schweiz